The Role of 2-Dimensional Speckle Tracking Echocardiography in prediction of significant coronary artery - H. Ibrahem , Sabah; subhi Hussein , Mustafa (Diyala Journal of Medicine, 2022)
Background:Speckle tracking echocardiography is new technique to evaluate left ventricular function Objective: To evaluate sensitivity and specificity of two dimension global longitudinal strain ( 2D-GLS) estimated by speckle tracking echocardiography (2D-STE) to predict the diagnosis and degree of severity of CAD( coronary artery disease) in patient suspected to have stable ischemic heart diseases (IHD). Patients and Methods: An observational cross-sectional study, patients underwent echocardiography (TTE), left ventricular (LV)systolic function were estimate initially, (calculate LVEF) then assessment of LV global and regional longitudinal strain (GLS) were calculated next.All patient underwent coronary angiography in the catheterization unite and according to the result of coronary angiography, we separated patients into two groups: one how have significant (≥70%) coronary arteries stenosis (group A),and another group with non- significant(<70%) coronary arteries stenosis (group B). The study was done in echocardiography unit and catheterization lab in Ibn-Albitar center of cardiac surgery, the study carried out from April 2018 to May 2019. Results: This study 93 patients were included , there is mean ages was (60.2 ±6.3) years, majority of cases were males (72.0%), 47.3% of all cases had ≥3 risk factors, and according to angiography study (67.7%) had significant CAD .The frequency of DM, dyslipidemia, and the occurrence of ≥3 risk factors were significantly elevated in group A(patients with significant coronary artery stenosis ) in comparison to the group B. Mean EF and GLS were considerably lower in group A related to group B. There was not much difference in GLS between single and two vessels involvement, however, the GLS value in three vessels was significantly lower compared to single and two vessels involvement. GLS were independent predictor of significant coronary artery stenosis, independent of the effect DM, dyslipidemia, and the presence of ≥3 concomitant risk factor. Conclusion: Assessment (GLS) value by 2D speckle tracking echocardiography is good test for predicating diagnostic and severity of coronary arteries diseases, global longitudinal strain had positive relationship with increasing number of stenotic coronary arteries, and provides high quantitative diagnostic information for detection of the CAD.